Synaphobranchid eel swarms on abyssal seamounts: Largest aggregation of fishes ever observed at abyssal depths. (January 2021) - Leitner, Astrid B.; Durden, Jennifer M.; Smith, Craig R.; Klingberg, Eric D.; Drazen, Jeffrey C.
Abstract: The abyssal seafloor makes up three quarters of the ocean floor, and it is generally characterized as a food-limited habitat with low numbers of megafauna, particularly fishes. Baited camera observations from three abyssal seamount summits in the equatorial Pacific challenge this idea. On each of two deployments at the southernmost seamount, over 100 synaphobranchid eels ( Ilyophis arx ) were recorded feeding on standard bait (1 kg mackerel). This is the highest number of fishes per kg of bait ever recorded below 1000 m, including observations from large organic falls such as cetacean and shark carcasses. It is also the highest number that has ever been recorded at carrion of any kind or size at abyssal depths. We suggest an abyssal 'seamount effect' may be responsible, highlighting the potential importance of seamounts in structuring abyssal communities. Highlights: Over 100 synaphobranchid eels were observed at a 1kg bait package deployed on an abyssal seamount summit in the southwestern Clarion-Clipperton Zone. Synaphobranchid eels, identified as Ilyophis arx, were exclusively observed on abyssal seamount summits, not on surrounding abyssal plains. This is the highest number of fishes ever recorded per kg of bait/carrion below 1000 m. This is the highest number of fishes that has ever been recorded at carrion of any kind or size at abyssal depths. An abyssal 'seamount' effect may be responsible.